Formulation of Approaches to Modeling Scenarios for Regulation of Imbalances in Socio-Economic Development of Regions - Shevchenko Olga V. (Problemi Ekonomiki, 2020)
The aim of the study is to create logical high-quality tools to analyze imbalances in regional development and further regulate such imbalances. The review of scientific works carried in the article showed the lack of comprehensive approach to analysis of the imbalances, their qualitative assessment and use, which is not least because of the impossibility of applying a simple mathematical apparatus to analyze a set of heterogeneous unordered dynamic data characterizing the imbalances. The paper proposes approaches to constructing and applying a cognitive imitation model for regulating the imbalances, with building a corresponding algorithm. The main factors forming imbalances in regional development are identified. The relations among these factors are studied by constructing causal links (a cognitive map). A system dynamics model that will form the basis for further elaboration of scenarios for regulating regional development imbalances is built. The proposed model and its implementation in the scenarios for regulating imbalances will bring about specific structural changes in the socio-economic sphere of regions and improve the balance of the economy and social sphere of a region. The originality of the study is due to the proposal to use the cognitive imitation model for regulating the imbalances to understand the trend in the development of the regional socio-economic system and forecast processes in regions.